2017
DOI: 10.15837/ijccc.2017.5.2930
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Social Network-based Collaborative Filtering Method for Personalized Manufacturing Service Recommendation

Abstract: Nowadays, social network-based collaborative filtering (CF) methods are widely applied to recommend suitable products to consumers by combining trust relationships and similarities in the preference ratings among past users. However, these types of methods are rarely used for recommending manufacturing services. Hence, this study has developed a hybrid social network-based CF method for recommending personalized manufacturing services. The trustworthy enterprises and three types of similar enterprises with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…For example, Fan et al [ 13 ] conducted service recommendation research from the perspective of manufacturing service clustering, developed a service clustering method by using a Latent Dirichlet Allocation-based topic model to cluster CMfg services into specific domains, and then introduced a domain-aware reputation service recommendation method to recommend highly reputable services in each domain for users. Zhang et al [ 41 ] developed a CF method based on hybrid social networks for recommending personalized manufacturing services. Hao et al [ 42 ] found that most of the traditional recommendation methods ignore the evolutionary characteristics of CMfg service systems, and for this problem, a time-aware target reconfiguration service description method was proposed, leading to a new recommendation strategy for manufacturing services.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Fan et al [ 13 ] conducted service recommendation research from the perspective of manufacturing service clustering, developed a service clustering method by using a Latent Dirichlet Allocation-based topic model to cluster CMfg services into specific domains, and then introduced a domain-aware reputation service recommendation method to recommend highly reputable services in each domain for users. Zhang et al [ 41 ] developed a CF method based on hybrid social networks for recommending personalized manufacturing services. Hao et al [ 42 ] found that most of the traditional recommendation methods ignore the evolutionary characteristics of CMfg service systems, and for this problem, a time-aware target reconfiguration service description method was proposed, leading to a new recommendation strategy for manufacturing services.…”
Section: Related Workmentioning
confidence: 99%
“…Influential related work efforts have utilized RSs to assist customers in identifying the manufacturing services (e.g., resources, capabilities) needed to accomplish the required manufacturing task [ 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Related Workmentioning
confidence: 99%
“…Some authors have used a hybrid recommendation method that integrates social network and collaborative filtering techniques to recommend manufacturing services [ 29 , 30 ]. By adopting collaborative filtering and social network techniques, the authors in [ 29 ] predicted the missing Quality of Services (QoS) values of manufacturing services.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation